Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean - Hogans, W. E. (Zootaxa, 2017)
The genus Pennella Oken, 1816, mesoparasitic copepods from marine fish and mammals, is reviewed with the objective of determining the validity of members of the genus. Details of the external morphological structures of the adult female are presented. Pennella species are differentiated based on a combination of characters: the type of host parasitized, overall length of the parasite, shape, size and configuration of cephalothoracic papillae, segmentation of the first and second antenna, holdfast horn number, shape and configuration, and structure of the abdominal plumes. A new species of Pennella, Pennella benzi sp. nov., is described from the escolar, Lepidocybium flavobrunneum in the northwest Atlantic. Pennella balaenoptera Koren & Danielssen, 1877 is reported from the harbor porpoise (Phocaena phocaena) in the Bay of Fundy, a new locality record. The validity of 44 species is assessed; nine species (P. balaenoptera Koren & Danielssen, 1877, P. benzi sp. nov., P. diodontis Oken, 1816, P. exocoeti (Holten, 1802), P. filosa Linnaeus, 1758, P. hawaiiensis Kazachenko & Kurochkin, 1974, P. instructa Wilson, 1917, P. makaira Hogans, 1988 and P. sagitta Linnaeus, 1758) are considered substantiated and valid; six species (P. elegans Gnanamuthu, 1957, P. longicauda Gnanamuthu, 1957, P. platycephalus Gnanamuthu, 1957, P. remorae Murray, 1856, P. robusta Gnanamuthu, 1957, and P. selaris Kirtisinghe, 1964) exhibit unique characteristics, but are based on descriptions of single specimens, have not been found since the original reports and are considered as species inquirendae; the remaining species are unsubstantiated and invalid based on inadequate or missing original descriptions, or are designated as synonyms of valid species. A key to the valid species of the genus is provided.